Ultrafast response of self-powered humidity sensor of flexible graphene oxide film. (February 2023) - Zeng, Songwei; Pan, Qiubo; Huang, Zhijing; Gu, Chenjie; Wang, Tao; Xu, Jinhui; Yan, Zihan; Zhao, Feiyu; Li, Pei; Tu, Yusong; Fan, Yan; Chen, Liang
Graphical abstract: Highlights: The GO humidity sensor fabricated by a simple way. The GO humidity sensor with ultrafast response and recovery time less than 0.3s. Protons generated from oxygen-containing groups and water molecules revealed. An array of sensors was successfully fabricated to demonstrate its application. LEDs lighted up by power-generating device made from humidity sensors. Abstract: Next-generation humidity sensor, as one of the smart devices in artificial skin or flexible electronics, will need to be self-powered, flexible, fast and accurately detecting in the microenvironment. Although various flexible humidity sensors have already been demonstrated, most of them rely on large external power sources to operate, and still suffer from slow response, poor selectivity in environmental stimuli, and expensive and complicated procedures. Here, we realize a self-powered humidity sensor with ultrafast response and recovery time of less than 0.3 s by flexible GO film. Importantly, of all state-of-the-art humidity sensors, this is the fastest response for humidity sensor. Moreover, the sensor has a high sensitivity within a wide range of RH from 33% to 98%, and an excellent selective response to humidity under multiple environmental stimuli, due to its moist-induced generator. Theoretical computations reveal that protons generated spontaneously from oxygen-containing groups and water molecules, have a fast diffusion behavior as Grotthuss hopping. In particular, we build four real-time measurement systems capable of respiration monitoring of human, smart leaf surface humidity sensor, and energy harvesting. Our work provides a simple way to fabricate next-generation self-powered sensor using GO film with outstanding humidity sensor performance.